Characterizing the composition of commercial black sea bass (Centropristis striata) catch and discards in the Mid-Atlantic and southern New England regions - Verkamp, Hannah J.; Soranno, Elizabeth A.; Bethoney, N. David (Frontiers in Marine Science, 2025)
Black sea bass (Centropristis striata) is an abundant fishery species that occupies continental shelf waters from the Gulf of Mexico to the Gulf of Maine. There has been a rapid northward shift in its center of biomass, contributing to an increase in fishing activity within the northern stock. Several research priorities have been identified for the species, including the need for a better understanding of the size of commercially caught fish, especially discards, and the catchability of black sea bass in different gear types to reduce uncertainty in the stock assessment. Here, we utilize fishery-dependent data collected by the Commercial Fisheries Research Foundation and Rhode Island Department of Environmental Management Black Sea Bass Research Fleet to address these needs. Throughout the Southern New England and Mid-Atlantic regions, 2,433 sampling sessions were completed over seven years by commercial fishermen using five gear types (trawl, gillnet, lobster-crab trap, fish pot, commercial rod and reel). Kruskal-Wallis and Kolmogorov-Smirnov tests and generalized additive models were applied to investigate differences in size composition among gear types and disposition, as well as temporal trends of landed, retained, and discarded fish. Results suggest that the size composition of black sea bass significantly differed among gear types and disposition. Depending on the gear type, a large proportion (25%-100%) of discarded fish were above the federal minimum commercial size limit. In addition, beyond the expected interannual variation in the size of black sea bass, there were no apparent positive or negative trends. The study’s results highlight the value of this cost-effective approach to quickly address data gaps for use in stock assessments while also engaging members of the fishing community.